A theoretical model of high Curie temperature for N-type ferromagnetic diluted semiconductors based on iron-doped indium antimonide - Mekuye, Bawoke; Abera, Birhanu (Frontiers in Physics, 2023)
In this paper, without using an external magnetic field, ferromagnetism on diluted InFeSb magnetic semiconductors is studied up to 317.65 K. The spin-wave model that the Heisenberg Hamiltonian translates into in the system has been developed using the green function formalism and the Holstein–Primakoff transformation estimate. The numbers of magnons, dispersion, Curie temperature, susceptibility, and specific heat capacity of the system have all been determined using the established model. The findings demonstrate that the ferromagnetic in In0.893Fe0.107Sb has a Curie temperature that is significantly higher than those found in prior investigations (317.65 K).